A mechanism for the efficient provision of Potential Pareto public goods (2023)
Providing a public good that causes a local harm to its host poses two problems previously unexplored together: where to locate it and how large it should be. We propose a mechanism combining some market-like properties with a modified second-price auction. The mechanism selects a host, a facility size, a compensation for hosting the project, and determines how the compensation is split among the non-hosts. If each community bids truthfully for becoming the host–a strategy from which no community has incentives to deviate–the selected allocation is globally optimal, even if communities’ preferences are private information. In contrast with the literature, the host pays the second-highest bid while receiving the market benefits to prevent distortions in the optimal size.